FAKTOR-FAKTOR YANG MEMPENGARUHI PENYALURAN KREDIT (Studi Pada Sektor Perbankan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2010-2012) - Savina Pravasti Rimawan, 10.05.52.0054; Nurhayati, Ida (Students Journal of Accounting and Banking, 2014)
This study analyzes the factors that affect credit of Non performing Loan (NPL), Capital Adequacy Ratio (CAR), Loan to Deposit Ratio(LDR), and Return On Assets (ROA). The data used in this study are listed banking companies in Indonesia Stock Exchange 2010-2012. These samples were selected using a method purposing sampling with a sample size of data 78. The method used in this study of multiple linear regression analysis to test the hypothesis that the t test and F test. Before using multiple regression analysis, performed classical assumption first. Based on the research, it can be conclude that NPL has negative and no significant effect on Credit, CAR has negative and significant effect on Credit, LDR has positive and no significant effect on Credit, and ROA has negative and significant effect on Credit. Simoultaneously there is a significant effect between NPL, CAR, LDR, and ROA to the volume of loans.Keywords: NPL, CAR, LDR, ROA, Credit